2010
DOI: 10.1002/cncr.25137
|View full text |Cite
|
Sign up to set email alerts
|

Is it useful to detect lymphovascular invasion in lymph node‐positive patients with primary operable breast cancer?

Abstract: BACKGROUND: Lymphovascular invasion (LVI) is a widely recognized prognostic factor in lymph node-negative breast cancers. However, there are only limited and controversial data about its prognostic significance in lymph node-positive patients. METHODS: Among 931 patients operated on and monitored at the authors' institution for an invasive breast carcinoma between 1989 and 1992, all 374 lymph node-positive breast cancers entered the study (median follow-up, 126 months). RESULTS: LVI was present in 46% of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
(23 reference statements)
5
20
1
1
Order By: Relevance
“…The same findings were reported in many previous studies [21][22][23][24] and from previous findings by our group. 2,7,8,15,25,26 The rate of LI in the current study was 47%, which lies in the same range as that reported in other studies: 28%, 20 46%, 13 and 55% 27 of patients with LN-positive BC in different patient cohorts. In our specimens, most of the LI lesions were detected in the peritumoral vessels (76% of LI-positive specimens).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The same findings were reported in many previous studies [21][22][23][24] and from previous findings by our group. 2,7,8,15,25,26 The rate of LI in the current study was 47%, which lies in the same range as that reported in other studies: 28%, 20 46%, 13 and 55% 27 of patients with LN-positive BC in different patient cohorts. In our specimens, most of the LI lesions were detected in the peritumoral vessels (76% of LI-positive specimens).…”
Section: Discussionsupporting
confidence: 88%
“…In a similar study that examined vascular invasion using H&E-stained sections in 374 LNpositive BC specimens, it was found to be an independent poor prognostic factor for development of DM. 13 To determine in more detail the prognostic significance of LI in subgroups of BC according to number of positive axillary LNs, patients were divided into four groups (patients with one, two, three and more than three positive LNs). LI was significantly associated with shorter OS, shorter DFI, and higher risk for DM in patients with single positive LN, but not with patients having two, three or more than three positive LNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its interpretation is sometimes difficult. Previous studies have shown that, in the patients with positive LVI, prognosis is abated and overall survival is decreased (Mohammed et al, 2007;Ragage et al, 2010). In this study, although LVI was positive in 42.9% of all MMGTs, there was no statistical relationship between HER-2 positivity and LVI.…”
Section: Discussioncontrasting
confidence: 69%
“…Other prognostic factors, such as age, tumor location, histological grade, ER, PR, radiotherapy and systemic treatments also had no prognostic signifi cance. Regrettably lymphatic vascular invasion was not evaluated for incomplete data in pathologic reports [23,24] .…”
Section: Discussionmentioning
confidence: 99%